1988
DOI: 10.1093/oxfordjournals.alcalc.a044830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Glucose on the Rate of Metabolism of Ethanol in Humans

Abstract: We have tested whether the effect of carbohydrate on the rate of alcohol metabolism can be reproduced by glucose alone. Ten male subjects were given ethanol by intravenous infusion until a steady state was established and 100 g glucose in solution was then taken orally. The rate of alcohol metabolism, measured as the rate of infusion required to maintain a constant breath alcohol reading, increased significantly after glucose but there were differences between the subjects. The presence or absence of a change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Dietary factors and nutritional status are well known to influence the effects of ethanol on health (Perry et al, 1995;Dreosti, 1993) and to alter ethanol pharmacokinetics (Mascord et al, 1998;Lumeng et al, 1979). In particular, it has been suggested that there may be a linear relationship between basal metabolic rate and the rate of ethanol metabolism (Lieber, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary factors and nutritional status are well known to influence the effects of ethanol on health (Perry et al, 1995;Dreosti, 1993) and to alter ethanol pharmacokinetics (Mascord et al, 1998;Lumeng et al, 1979). In particular, it has been suggested that there may be a linear relationship between basal metabolic rate and the rate of ethanol metabolism (Lieber, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been suggested that there may be a linear relationship between basal metabolic rate and the rate of ethanol metabolism (Lieber, 1991). Studies following consumption of a carbohydrate rich meal have demonstrated acutely increased ethanol metabolism (Mascord et al, 1998), while fasting has been reported to reduce ethanol oxidation (Lumeng et al, 1979). Since pregnant rats consume significantly greater calories than non-pregnant rats, we used the TEN system to control caloric intake and examined UECs in rats infused ethanol-containing diets at appropriate caloric intake for non-pregnant and pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that the rate of alcohol metabolism differs from person to person (Pratt and Taylor, 1990), maintenance of BAC at a constant level during an alcohol infusion session in humans requires monitoring breath or blood alcohol levels during the session in each individual and repeatedly adjusting the alcohol delivery rate so that the rate of delivery matches the alcohol elimination rate for that individual Ramchandani et al, 1999b). A continuous alcohol infusion procedure for clamping BAC in humans has been used to examine ethnic and sex differences in alcohol metabolism (Kwo et al, 1998), the development of withinsession alcohol tolerance (Jäntti et al, 1983;Lehtinen et al, 1981;O'Connor et al, 1998;Ramchandani et al, 1999c), and the effect of food and glucose intake on alcohol metabolism (Mascord et al, 1988(Mascord et al, , 1991Ramchandani et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of ethanol metabolism was doubled in subjects fed a meal during the ethanol postabsorptive period versus fasted subjects (Miller and Stirling, 1965). More recently, a high carbohydrate meal (Rogers et al, 1987) and an oral glucose (Mascord et al, 1988) or fructose (Mascord et al, 1991) solution were shown to significantly increase the rate of metabolism of ethanol as determined by an increase in the intravenous ethanol required to maintain a constant BAL.…”
mentioning
confidence: 99%